Recent advances in compatibility and toughness of poly(lactic acid)/poly(butylene succinate) blends - Zhao Xipo (De Gruyter, 2021)
Poly(butylene succinate) (PBS) has good impact strength and high elongation at break. It is used to toughen biodegradable poly(lactic acid) (PLA) materials because it can considerably improve the toughness of PLA without changing the biodegradability of the materials. Therefore, this approach has become a hotspot in the field of biodegradable materials. A review of the physical and chemical modification methods that are applied to improve the performance of PLA/PBS blends based on recent studies is presented in this article. The improvement effect of PLA/PBS blends and the addition of some common fillers on the physical properties and crystallization properties of blends in the physical modification method are summarized briefly. The compatibilizing effects of nanofillers and compatibilizing agents necessary to improve the compatibility and toughness of PLA/PBS blends are described in detail. The chemical modification method involving the addition of reactive polymers and low-molecular-weight compounds to form cross-linked/branched structures at the phase interface during in situ reactions was introduced clearly. The addition of reactive compatibilizing components is an effective strategy to improve the compatibility between PLA and PBS components and further improve the mechanical properties and processing properties of the materials. It has high research value and wide application prospects in the modification of PLA. In addition, the degradation performance of PLA/PBS blends and the methods to improve the degradation performance were briefly summarized, and the development direction of PLA/PBS blends biodegradation performance research was prospected.